Introduction of Rosa spinosissima L., its form 'Double White' and cultivars in M.M. Grishko National Botanical Gardens of the NAS of Ukraine - O.L. Rubtsova; V.I. Chizhan'kova (Інтродукція Рослин, 2002)
The results of introduction of Rosa spinosissima L., its form 'Double While' and its three cultivars have been generalized. Their botanical description have been given and their biological peculiarities have been described The perspectives of cultivation of the studied taxons have been determined.